Characterization of Jos City Road Network, Nigeria - Olumide Akinwumi Oluwole; Nwanret Gideon Daful (Indonesian Journal of Geography, 2014)
ἀe performance of road network depends on its topological characteristics which help to deḀne its connectiv-ity. ἀis paper analyses the topological characteristic of Jos city road network and its bearing on traᴀc ᰀow situations. Simple graph theoretic measures oᬀered the framework on which the problem was approached. ἀe study requires the abstraction and analysis of the topological structure by selection of certain variables relating to the road connectivity. ἀese include the Beta, Gamma and Alpha index, the PI, Cyclomatic number, and the spread and density of the network. Information on these variables was obtained through the use of vector data model to abstract the road network graph from the Quick-bird satellite imagery used for the study. Results of the Ḁndings reveal that, the road network of Jos City Centre as a whole have achieved an average level of connectivity, showing Beta index values of 1.4049, Gamma index value of 47.06%, Alpha index Value of 20.63%; and a pi and cyclomatic number of 24.74 and 165 respectively, the spread of the network is moderate exhibiting a value of 23, even though some areas have more concentration of roads than the others; and has a road density of 52 links per km2. Based on these Ḁndings, the need for construction of new roads is imperative so as to improve the eᴀciency of connectivity and accessibility within the city.